Retrieval of target structure information from laser-induced photoelectrons by few-cycle bicircular laser fields - Hoang, Van-Hung; Le, Van-Hoang; Lin, C. D.; Le, Anh-Thu (My University, 2017)
By analyzing theoretical results from a numerical solution of the time-dependent Schrödinger equation for atoms in few-cycle bicircular laser pulses, we show that high-energy photoelectron momentum spectra can be used to extract accurate elastic scattering differential cross sections of the target ion with free electrons. We find that the retrieval range for a scattering angle with bicircular pulses is wider than with linearly polarized pulses, although the retrieval method has to be modified to account for different returning directions of the electron in the continuum. This result can be used to extend the range of applicability of ultrafast imaging techniques such as laser-induced electron diffraction and for the accurate characterization of laser pulses.